NMF-NAD:detecting network-wide traffic anomaly based on NMF - Xiang-lin WEI; Ming CHEN; Guo-min ZHANG; Jian-jun HUANG (Tongxin xuebao)
A non-negative matrix factorization (NMF) based network wide traffic anomalies detection (NMF-NAD) method was proposed.NMF-NAD firstly reconstructed the traffic matrix in the non-negative sub-space,and then detected the anomalies through Shewhart control chart based on the reconstruction error.Experimental results on both simulation and Abilene data show that NMF-NAD can achieve high detection accuracy with low complexity.